2012
DOI: 10.1210/jc.2012-1499
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cortisol Stress Response to Sedation and Anesthesia in Children

Abstract: Sedation and anesthesia can induce a significant rise in cortisol in children. Additional studies should be performed to validate our results and to determine whether stress dosing of corticosteroids may be needed for children with adrenal insufficiency undergoing sedated procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Our results are in line with previously reported perioperative cortisol response during carotid endarterectomy (CEA) performed in LA and GA [21]. Accordingly, a study observing perioperative salivary cortisol levels in response to varying levels of sedation found that 25% of patients had a fourfold increase in salivary cortisol levels and mean cortisol values increased more than threefold from baseline if surgical intervention was performed in LA [13]. In contrast to these findings, Hill and Walker investigated the salivary cortisol levels in patients undergoing third molar removal under LA and GA. Their results showed that patients treated in LA showed lower levels of stress response than those having treatment in GA [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with previously reported perioperative cortisol response during carotid endarterectomy (CEA) performed in LA and GA [21]. Accordingly, a study observing perioperative salivary cortisol levels in response to varying levels of sedation found that 25% of patients had a fourfold increase in salivary cortisol levels and mean cortisol values increased more than threefold from baseline if surgical intervention was performed in LA [13]. In contrast to these findings, Hill and Walker investigated the salivary cortisol levels in patients undergoing third molar removal under LA and GA. Their results showed that patients treated in LA showed lower levels of stress response than those having treatment in GA [22].…”
Section: Discussionsupporting
confidence: 92%
“…All patients of age undergoing a sentinel lymph node excision at the Department of Dermatology, University Hospital Essen, Germany, due to a melanoma of stages I and II according to AJCC 2009 (American Joint Committee on Cancer) could be included in our prospective study. Exclusion criteria included intake of glucocorticoids or psychotropic medication during the former 6 months, pregnancy, age under 18 years, and BMI ≥ 30 as salivary cortisol levels were reported to be significantly impacted by obesity and might confound results [13]. We calculated with two groups of the same size to determine the sample size by means of the independent t test: group 1 = group 2, standard deviation 1 = standard deviation 2.…”
Section: Patients and Sample Size Calculationmentioning
confidence: 99%
“…We have used pragmatic measures of total cortisol, CBG and FCI, as they are of more practical utility to clinicians. Salivary cortisol may be an alternative measure of free cortisol levels: this has been used in the context of paediatric surgery and oral surgery, but its utility has not yet been explored in this context. Second, we have not measured ACTH levels, which are known to rise during surgery and general anaesthesia, as this study was intended to assess the cortisol response to inform recommendations for replacement in hypoadrenal patients.…”
Section: Discussionmentioning
confidence: 99%
“…A threefold to sevenfold increase in cortisol concentrations has been described during anaesthesia or sedation 49 50. In contrast, no cortisol rise was observed in a study of 30 healthy children undergoing elective urological procedures (eg, circumcision, orchidopexy, hypospadias repair, nephrectomy), although cortisol concentrations were noted to rise an hour following surgery 51.…”
Section: Cortisol Replacement Therapy In Childhood and Adolescencementioning
confidence: 97%